Classification of production factors of foundry production - A. M. Lazarenkov (Литьë и металлургия)
The classification of production factors of working conditions at the workplaces of the main equipment used in the foundry is given. This classification is developed on the basis of the results of the conducted research and based on the materials given in the domestic and foreign literature.This allows us to evaluate the technological processes and equipment used in the design and reconstruction of foundries (sections) to ensure the most favorable working conditions.